Die samehang tussen godsdienskritiek en samelewingskritiek by Karl Marx - A. Pelser (Koers : Bulletin for Christian Scholarship, 1988)
In this article it is reasoned that the classical Marxist critique of religion cannot be regarded as critique of religion per se. M arx’s critique of religion is embedded in his societal critique and any effort to analyse and /o r interpret his critique of religion should be done from the vantage point of his societal critique . Seeing that Marx's critique of religion is an essential function of his critique on capitalist society, it cannot simply by default be dismissed as an atheist onslaught on religion. As a sub section of his societal critique an evaluation of Marx's critique of religion should above all focus on his arguments which centre on the functional relationship between church and state. It is only in this way that one can account for Marx's critique of religion not being in the first place an atheist onslaught on religion, b u t can see it functioning fundamentally as a critique on the politico-theological arena; thus as a critique for the sake of man and on those aspects/links which deter him in his effort to attain full self-realisation.